Opportunities for improving the efficiency of paediatric HIV treatment programmes. - Revill, P; Walker, S; Mabugu, T; Nathoo, K; Mugyenyi, P; Kekitinwa, A; Munderi, P; Bwakura-Dangarembizi, M; Musiime, V; Bakeera-Kitaka, S; Nahirya-Ntege, P; Walker, A; et al. (Lippincott, Williams and Wilkins, 2015)
Objectives: To conduct two economic analyses addressing whether to: routinely monitor HIV-infected children on antiretroviral therapy (ART) clinically or with laboratory tests; continue or stop cotrimoxazole prophylaxis when children become stabilized on ART. Design and methods: The ARROW randomized trial investigated alternative strategies to deliver paediatric ART and cotrimoxazole prophylaxis in 1206 Ugandan/Zimbabwean children. Incremental cost-effectiveness and value of implementation analyses were undertaken. Scenario analyses investigated whether laboratory monitoring (CD4 tests for efficacy monitoring; haematology/biochemistry for toxicity) could be tailored and targeted to be delivered cost-effectively. Cotrimoxazole use was examined in malaria-endemic and non-endemic settings. Results: Using all trial data, clinical monitoring delivered similar health outcomes to routine laboratory monitoring, but at a reduced cost, so was cost-effective. Continuing cotrimoxazole improved health outcomes at reduced costs. Restricting routine CD4 monitoring to after 52 weeks following ART initiation and removing toxicity testing was associated with an incremental cost-effectiveness ratio of 6084 dollars per quality-adjusted life-year (QALY) across all age groups, but was much lower for older children (12+ years at initiation; incremental cost-effectiveness ratio = 769 dollars/QALY). Committing resources to improve cotrimoxazole implementation appears cost-effective. A healthcare system that could pay 600 dollars/QALY should be willing to spend up to 12.0 dollars per patient-year to ensure continued provision of cotrimoxazole. Conclusion: Clinically driven monitoring of ART is cost-effective in most circumstances. Routine laboratory monitoring is generally not cost-effective at current prices, except possibly CD4 testing amongst adolescents initiating ART. Committing resources to ensure continued provision of cotrimoxazole in health facilities is more likely to represent an efficient use of resources.